Silver-sepiolite (Ag-Sep) hybrid reinforced active gelatin/date waste extract (DSWE) blend composite films for food packaging application. (1st February 2022) - Rangaraj, Vengatesan M.; Devaraju, Subramani; Rambabu, K.; Banat, Fawzi; Mittal, Vikas
Graphical abstract: Highlights: Active gelatin composite films developed using Ag-Sep hybrid additive. Ag-Sep improved the water barrier properties of active gelatin films. Ag-Sep contributes sustainable release of active compounds from film to simulant. Ag-Sep improved the antimicrobial efficacy of the gelatin blend film. Abstract: In this study, date syrup waste extract (DSWE) (15 wt%) and different content of silver doped sepiolite hybrid (Ag-Sep, 0.25–3 wt%) were incorporated into gelatin matrix to develop a series of active composite packaging films. Incorporating 2 wt% of Ag-Sep increased the modulus of blend film by 98% compared to unmodified gelatin/DSWE blend film. The active gelatin composite film exhibited superior active compounds migration to aqueous food simulants. Besides, Ag-Sep provided a tortuous pathway to the composite film, resulting in high 2, 2-diphenyl-1-picrylhydrazyl (DPPH) radical inhibition efficiency (91%) and slow-release kinetics of active compounds to the food simulant. The Ag-Sep hybrid was improved the antimicrobial property of the gelatin/DSWE blend film against both gram-negative and gram-positive microbes. Thus, this study demonstrated that the Ag-Sep hybrid exhibits significant properties in the active gelatin composite films, implying that this hybrid could be an effective additive for various active packaging films.